Stroke increases ischemia-related decreases in motor unit discharge rates - Murphy, Spencer A. (J Neurophysiol, 2018)
Following stroke, hyperexcitable sensory pathways, such as the group III/IV afferents that are sensitive to ischemia, may inhibit paretic motor neurons during exercise. We quantified the effects of whole leg ischemia on paretic vastus lateralis motor unit firing rates during submaximal isometric contractions. Ten chronic stroke survivors (>1 yr poststroke) and 10 controls participated. During conditions of whole leg occlusion, the discharge timings of motor units were identified from decomposition of high-density surface electromyography signals during repeated submaximal knee extensor contractions. Quadriceps resting twitch responses and near-infrared spectroscopy measurements of oxygen saturation as an indirect measure of blood flow were made. There was a greater decrease in paretic motor unit discharge rates during the occlusion compared with the controls (average decrease for stroke and controls, 12.3 ± 10.0% and 0.1 ± 12.4%, respectively; P < 0.001). The motor unit recruitment thresholds did not change with the occlusion (stroke: without occlusion, 11.68 ± 5.83%MVC vs. with occlusion, 11.11 ± 5.26%MVC; control: 11.87 ± 5.63 vs. 11.28 ± 5.29%MVC). Resting twitch amplitudes declined similarly for both groups in response to whole leg occlusion (stroke: 29.16 ± 6.88 vs. 25.75 ± 6.78 Nm; control: 38.80 ± 13.23 vs 30.14 ± 9.64 Nm). Controls had a greater exponential decline (lower time constant) in oxygen saturation compared with the stroke group (stroke time constant, 22.90 ± 10.26 min vs. control time constant, 5.46 ± 4.09 min; P < 0.001). Ischemia of the muscle resulted in greater neural inhibition of paretic motor units compared with controls and may contribute to deficient muscle activation poststroke. NEW & NOTEWORTHY Hyperexcitable inhibitory sensory pathways sensitive to ischemia may play a role in deficient motor unit activation post stroke. Using high-density surface electromyography recordings to detect motor unit firing instances, we show that ischemia of the exercising muscle results in greater inhibition of paretic motor unit firing rates compared with controls. These findings are impactful to neurophysiologists and clinicians because they implicate a novel mechanism of force-generating impairment poststroke that likely exacerbates baseline weakness.